Text corpus: Academic texts – Humanities - Forsberg, Markus; Swedish Language Bank, University of Gothenburg (University of Gothenburg, 2021)
A corpus with academic texts (14,471,177 tokens, 673,820 sentences). This corpus can be searched through the Språkbanken Korp interface: http://spraakbanken.gu.se/korp/#lang=eng.

Licens: CC-BY

En korpus med akademiska texter inom humaniora (14 471 177 tokens, 673 820 meningar). Denna korpus är sökbar via Språkbankens Korp-gränssnitt: http://spraakbanken.gu.se/korp.

Licens: CC-BY
Textkorpus: Akademiska texter – Humaniora
Keywords: linguistics; lingvistik; linguistic analysis; lingvistisk analys; humanities education; humaniora; Language and linguistics; Språk och lingvistik; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik